(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The purpose of this research is to investigate the psychological and mental consequences of unemployment on Unemployed in Lattakia in 2016. The population consists of unemployed people whose age is between 15 and 64 years. The GHQ-12 questionnaire has employed in order to assess the psychological and mental health of unemployed people. The results showed that unemployment has negative effects on the psychological and mental health of unemployed people. Unemployment leads unemployed to feel: inability to concentrate, loosing much sleep over worry, not playing a useful part in things, not capable of making decisions about things, constantly under strain, could not overcome difficulties, not able to enjoy normal day-to-day activities, not able to face up problems, unhappy or depressed, losing confidence in self, thinking as worthless person, unhappy. The results showed, also, that “divorced’ unemployed person has more psychological and mental problems comparing with “single” unemployed person. In addition, unemployed person who lives in rent or mortgage house has more psychological and mental problems comparing with unemployed person who own his house. The educational degree has played also a role in the differences. أثر البطالة في الصحة النفسية والذهنية للمتعطلين عن العمل في محافظة اللاذقية يهدف هذا البحث إلى دراسة أثر البطالة في الصحة النفسية والذهنية للمتعطلين عن العمل في محافظة اللاذقية في عام 2016. يتكون مجتمع البحث من جميع المتعطلين عن العمل في محافظة اللاذقية الذين تتراوح أعمارهم بين 15-64 سنة. أما عينة الدراسة فقد شملت 384 متعطل عن العمل. تم استخدام استبانة الصحة العامة بنسختها المختزلة GHQ-12لتقييم الصحة النفسية والذهنية للمتعطلين عن العمل. توصلت الدراسة إلى أن البطالة تؤثر سلبياً في الصحة النفسية والذهنية للمتعطل عن العمل، إذ تؤدي إلى: عدم التركيز، السهر نتيجة القلق، عدم لعب دور مفيد، عدم القدرة على اتخاذ القرارات، شعور الشخص بأنه تحت الضغط، عدم القدرة على الاستمتاع بالأنشطة اليومية، عدم القدرة على مواجهة المشاكل، الشعور بالحزن أو الاكتئاب، وعدم الشعور بالسعادة. وقد تم التوصل إلى أن "المطلق أو المطلقة" يعانون من الآثار النفسية والذهنية للبطالة أكثر من "العازب أو العازبة"، وأن المتعطل عن العمل سواء أكان مستأجراً أم كان يقطن في بيت رهن يتعرض للأعراض النفسية والذهنية بشكل أكبر من المتعطل عن العمل ممن يملك منزلاً. كما لعب المستوى التعليمي دوراً في الفروقات.